Anaemia in the Hospitalized Elderly in Tanzania: Prevalence, Severity, and Micronutrient Deficiency Status. (26th February 2021) - Chamba, Clara; Nasser, Ahlam; Mawalla, William F.; Masamu, Upendo; Budodi Lubuva, Neema; Tebuka, Erius; Magesa, Pius
Abstract : Introduction . Anaemia is a common problem in sub-Saharan Africa. While most literature has focused on children, women of childbearing age, and pregnant women, data for the elderly population are relatively scarce. Anaemia exhorts negative consequences to functional ability of elderly patients, both physically and cognitively. The purpose of this study was to determine the prevalence of anaemia, severity, and micronutrient deficiency status in the elderly hospitalized patients in Tanzania. Methods . A total of 156 hospitalized adults aged 60 years and above were enrolled in this study. A structured questionnaire was used to capture sociodemographic and clinical characteristics. Blood samples were collected, and a complete blood count, serum cobalamin, serum ferritin, and serum folate levels were measured to assess anaemia and micronutrient deficiency status in all participants who had anaemia. Results . The prevalence of anaemia was 79.5% (124/156) with severe anaemia in 33.9% (42/124) of participants, moderate anaemia in 42.7% (53/124) of participants, and 23.4% (29/124) of all participants had mild anaemia. Micronutrient deficiency was found in 14.5% (18/124) of all participants with anaemia. Combined deficiency (either iron and vitamin B12 deficiency or iron and folate deficiency) was the most common micronutrient deficiency anaemia with a frequency of 33.3% (6/18), followed by isolated iron and folate deficiencies at equal frequency of 27.8% (5/18) and vitamin B12 deficiency at 11.1% (2/18). Conclusion . The prevalence of anaemia in the hospitalized elderly population is high warranting public health attention and mostly present in moderate and severe forms. Micro-nutrient deficiency anaemia is common in this age group and is mostly due to combined micronutrient deficiency.